2022
DOI: 10.1186/s12711-022-00761-3
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding and pedigree analysis of the European red dairy cattle

Abstract: Background Red dairy cattle breeds have an important role in the European dairy sector because of their functional characteristics and good health. Extensive pedigree information is available for these breeds and provides a unique opportunity to examine their population structure, such as effective population size, depth of the pedigree, and effective number of founders and ancestors, and inbreeding levels. Animals with the highest genetic contributions were identified. Pedigree data included 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…The pedigree-based study of Estonian dairy cows revealed that the average inbreeding coefficient of cows born in 2009-2018 was low (F = 0.023) [20]. However, this value is higher than the F = 0.015 for a large European red dairy cattle population [21] and lower than F = 0.052 found for Dutch-Flemish Holstein-Friesians [11]. Since breeding goals can be achieved by using the best-rated genetic material, breeders prefer to select from a limited number of elite bulls, and inbreeding is expected to increase.…”
Section: Introductionmentioning
confidence: 99%
“…The pedigree-based study of Estonian dairy cows revealed that the average inbreeding coefficient of cows born in 2009-2018 was low (F = 0.023) [20]. However, this value is higher than the F = 0.015 for a large European red dairy cattle population [21] and lower than F = 0.052 found for Dutch-Flemish Holstein-Friesians [11]. Since breeding goals can be achieved by using the best-rated genetic material, breeders prefer to select from a limited number of elite bulls, and inbreeding is expected to increase.…”
Section: Introductionmentioning
confidence: 99%